In Vitro Induction of Human Regulatory T Cells Using Conditions of Low Tryptophan Plus Kynurenines. Issue 12 (14th June 2017) - Hippen, K. L.; O'Connor, R. S.; Lemire, A. M.; Saha, A.; Hanse, E. A.; Tennis, N. C.; Merkel, S. C.; Kelekar, A.; Riley, J. L.; Levine, B. L.; June, C. H.; Turka, L. A.; et al.
Abstract : Thymic regulatory T cells (tTregs) and induced regulatory T cells (iTregs) suppress murine acute graft‐versus‐host disease (GVHD). Previously, we demonstrated that the plasmacytoid dendritic cell indoleamine 2, 3‐dioxygenase (IDO) fosters the in vitro development of human iTregs via tryptophan depletion and kynurenine (Kyn) metabolites. We now show that stimulation of naïve CD4 + T cells in low tryptophan (low Trp) plus Kyn supports human iTreg generation. In vitro, low Trp + Kyn iTregs and tTregs potently suppress T effector cell proliferation equivalently but are phenotypically distinct. Compared with tTregs or T effector cells, bioenergetics profiling reveals that low Trp + Kyn iTregs have increased basal glycolysis and oxidative phosphorylation and use glutaminolysis as an energy source. Low Trp + Kyn iTreg viability was reliant on interleukin (IL)‐2 in vitro . Although in vivo IL‐2 administration increased low Trp + Kyn iTreg persistence on adoptive transfer into immunodeficient mice given peripheral blood mononuclear cells to induce GVHD, IL‐2–supported iTregs did not improve recipient survival. We conclude that low Trp + Kyn create suppressive iTregs that have high metabolic needs that will need to be addressed before clinical translation. Abstract : This work defines the clinical‐scale production of Tregs induced via in vitro expansion of effector T cells under conditions of low tryptophan plus kynurenines that are as suppressive in vitro as thymic Tregs, but have high metabolic demands that hinder in vivo efficacy.